"Alone together forever", hope in the desire for companionship in Samuel Beckett's plays - Khoirunnisaa Abdul Ja’afar (2015)
This thesis reconciles the contradiction between the two ways of reading Beckett’s Waiting for Godot, Come and Go, Ohio Impromptu, and Krapp’s Last Tape by proving that hope stems not from the relief of knowing that the world is still familiar. Rather Beckett’s plays are hopeful because they display his characters’ struggle to reach out to one another, which exhibits their desire for companionship. Reading his plays through Abramovic’s performance provides a new perspective to reconsider the notion of hope in his work. By being silent and by freezing time in her performance, Abramovic bridges the gap between herself and her audience. Despite being entrapped in a meaningless and alien world, Beckett’s characters too strive to find a connection with one another. Reading Beckett’s work from this perspective reveals its timelessness as it addresses and provides a kind of consolation for the problem Man is faced with today; which is human beings’ alienation from one another and the problem of loneliness that displays our desire for companionship.